Peningkatan Ekspresi Matrix Metalloproteinase-9 Ligamentum Sacrouterina dan Otot Levator Ani Postpartum Rattus Norvegicus - Novida Ariani (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2021)
Background: Vaginal delivery is a risk factor for pelvic organ prolapse. The biomolecular mechanism that links it is still unclear, thought to be through Matrix Metalloproteinase 9 (MMP-9). Purpose: This study aims to determine the increase in MMP-9 in the supporting tissues of the pelvic organs, especially the sacrouterine ligament and levator ani muscles in the postpartum period. Methods: This study was an observational cohort study on 5 female rats of Rattus norvegicus Wistar strain. Which were divided into nulliparous groups, postpartum day 1, day 3, and day 7. MMP-9 expression was calculated and analyzed using ANOVA. Results: There was a significant difference (p=0.01) of MMP-9 expression in the sacrouterine ligament between nulliparous rats, postpartum day 1, day 3, and day 7. There was also a significant difference (p=0.00) levator ani muscle MMP-9 expression between nulliparous rats, postpartum day 1, day 3, and day 7. There was a trend of increasing MMP-9 expression on the 1st to 3rd day postpartum, then decreasing gradually on the 7th day. Conclusion: Delivery changes the expression of MMP-9 in pelvic floor tissues such as the sacrouterine ligament and levator ani muscle and these changes are time-dependent.Abstrak. Latar Belakang: Persalinan pervaginam merupakan faktor resiko prolaps organ panggul. Mekanisme biomolekuler yang menghubungkannya masih belum jelas, diduga melalui perantaraan Matriks Metalloproteinase 9 (MMP-9). Tujuan: Penelitian ini bertujuan untuk mengetahui peningkatan MMP-9 pada jaringan penyokong organ panggul, terutama ligamentum sacrouterina dan otot levator ani periode post partum. Metode: Penelitian ini adalah studi observational cohort pada 5 tikus betina Rattus norvegicus strain Wistar. Yang terbagi menjadi kelompok nullipara, postpartum hari ke-1, hari ke-3 dan hari ke-7.. Preparat jaringan ligamentum sacrouterina dan otot levator ani diwarnai dengan imunohistokimia. Ekspresi MMP-9 dihitung dan dianalisa dengan menggunakan ANOVA. Hasil: Terdapat perbedaan yang signifikan (p=0,01) ekspresi MMP-9 pada ligamentum sacrouterina antara tikus nullipara, postpartum hari ke-1, hari ke-3, dan hari ke-7. Terdapat pula perbedaan yang signifikan (p=0,00) ekspresi MMP-9 otot levator ani antara tikus nullipara , postpartum hari ke-1, hari ke-3, dan hari ke-7. Tampak tren peningkatan ekspresi MMP-9 pada hari ke-1 hingga ke-3 postpartum, selanjutnya menurun bertahap pada hari ke-7. Simpulan: Persalinan mengubah ekspresi MMP-9 pada jaringan dasar panggul seperti ligamentum sacrouterina dan otot levator ani dan perubahan ini bersifat time-dependently.